Food Waste Management System - AZHAR, NUR AIN AFIQAH; Sukadarin, Ezrin Hani (Progress in Engineering Application and Technology, 2025)
This project focuses on managing food waste in the workplace, with the aim of reducing food waste caused by improper disposal. The project emphasizes tracking and improving food waste management through data collected in a dashboard. This dashboard displays the flow of food waste, showing whether it increases or decreases on a monthly basis. To reduce food waste sent to landfills, the workplace has implemented a composting system, where food waste is sent to a vendor to be turned into fertilizer. At the end of each month, the vendor returns the processed fertilizer to the workplace. The process begins with the workplace providing labeled bins for food waste and general waste, raising awareness among employees. Employees are encouraged to sort waste according to the labels. Food waste is then weighed using a weighing machine, and the data is collected for the dashboard. Finally, the composted food waste is sent to the vendor, and the workplace receives fertilizer in return. The findings demonstrate that food waste can be effectively managed, and the flow of waste can be clearly monitored through the dashboard. The data highlights trends in food waste, such as increases or decreases in specific months, and helps identify the reasons behind these changes. Ultimately, this project raises awareness among employees about the importance of proper food waste management and provides guidelines for safe disposal practice.